2021
DOI: 10.3390/v13101932
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Salmonella Bacteriophage S1 Delivered and Released by Alginate Beads in a Chicken Model of Infection

Abstract: Modern bacteriophage encapsulation methods based on polymers such as alginate have been developed recently for their use in phage therapy for veterinary purposes. In birds, it has been proven that using this delivery system allows the release of the bacteriophage in the small intestine, the site of infection by Salmonella spp. This work designed an approach for phage therapy using encapsulation by ionotropic gelation of the lytic bacteriophage S1 for Salmonella enterica in 2% w/v alginate beads using 2% w/v ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
10
2
Order By: Relevance
“…Albany . Gomez-Garcia et al ( 2021 ) showed that Salmonella phage S1 showed high EOP on S. Pullorum, S . Gallinarum, and S .…”
Section: Discussionmentioning
confidence: 99%
“…Albany . Gomez-Garcia et al ( 2021 ) showed that Salmonella phage S1 showed high EOP on S. Pullorum, S . Gallinarum, and S .…”
Section: Discussionmentioning
confidence: 99%
“…focus on the use of phages in various food matrices, that is, raw and ground poultry meat (Duc et al, 2018;Grant et al, 2017), milk (Huang et al, 2018;Islam et al, 2020b), juices, lettuce (Islam et al, 2019), eggs (Sonalika et al, 2020), iceberg lettuce and cucumber (Bai et al, 2019a), and the elimination of biofilms formed on surfaces in food processing plants (Islam et al, 2019;Islam et al, 2020a). The latest reports also indicate phage improvement strategies in terms of increasing their survival in the digestive tract of animals and under food processing conditions (Gomez-Garcia et al, 2021). In the context of specific food matrices, Huang et al (2018) searched for highly effective phages against S. Typhimurium in milk, sausage, and lettuce.…”
Section: Referencementioning
confidence: 99%
“…Several approaches are used to protect phages from the undesirable effects of many food ingredients, such as organic acids, fatty acids, tannins, or the low pH of the gastrointestinal tract of animals (Xu 2021a). In the study of Gomez-Garcia et al (2021), encapsulation (ionotropic gelation, alginate beads, calcium chloride, and bacteriophage S1 against S. enterica) was used as a novel approach to phage delivery in an in vivo chicken model. The aim of encapsulation was to protect the phage against the low pH of the stomach and to release it at a higher pH.…”
Section: Phage Formulations To Enhance the Effectiveness Of Phage Act...mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, antibiotics are used to prevent and treat Salmonella infections, however, the preventive administration of antibiotics can lead to the emergence of multidrug resistance that has become a major global health concern, affecting the food chain, too (Galie et al, 2018, Jajere, 2019, Li et al, 2020, Vikram et al, 2020, Gomez-Garcia et al, 2021, Kuźmińska-Bajor et al, 2021. On the other hand, in line with the so-called "one health" approach, prevention of contamination and supply of safe food are top-priority issues to controlling and curbing the prevalence of foodborne pathogens (Vikram et al, 2020).…”
Section: Introductionmentioning
confidence: 99%